Cartographic model to determine optimal areas for the urban expansion of the Huanuco district as a contribution to the planning - Javier Silva, Luz Alexandra (2018)
The investigation was based on the analysis of the association of the space-time component using the Geographic Information Systems with associated information (graphic-tabular), allowing the application of spatial calculations, through the hierarchical analytical process; obtaining numerical answers, and resulting in 06 areas, by means of a selection model; that meet the conditions for population settlement, taking into account the interaction of the factors: Physical, (Pending, Dangers, Geology, Geomorphology and Rivers) and Socioeconomic (Roads, Airport, Health Centers, Educational Institutions, Tourism and Recreation Areas ) of which; The physical factor is the most influential during the urbanization process as it is a condition for urban growth, increasing vulnerability due to the increase and pressure of urbanization.Concluding, two of the areas selected by the model were classified: “Area 004” and “Area 005” as “Optimums”, which meet the ideal conditions for urban expansion in the Huánuco district as a contribution to planning.